Crystal structure refinement and vibrational analysis of Y[CO(CN)6].4H2O and its thermal decomposition products - Gil, Diego Mauricio (2013)
Studies on Y[Co(CN)6]·4H2O by means of thermal analysis, IR and Raman spectroscopy and X-ray powder diffraction were carried out. The complex Y[Co(CN)6]·4H2O crystallizes in the orthorhombic crystal system, space group Cmcm. Y3+ ion is eight-coordinated forming bicapped distorted trigonal prism YN6O2 and Co3+ ion is octahedrally coordinated to six CN groups. The IR spectrum shows well-resolved bands in the CN stretching region due to the presence of 13C and 15N in relative natural abundance. The Raman spectrum of the complex shows two distinct set of bands of the CN stretching vibration: one is a singlet and the other is split due to the low symmetry of the Y3+ ion compared to the pentahydrate complex. The thermal decomposition was studied in order to investigate the formation of YCoO3. The crystal structure of YCoO3 was refined by means of Rietveld analysis using PXRD data. We found that it was slightly deficient in Y3+, which is in agreement with the small amount of Y2O3 found as impurity in the sample. The formula of the mixed oxide obtained by this method of synthesis is Y0.961CoO3.